Recent Advances in Pharmacotherapeutic Approaches for Alopecia areata: A Systematic Review of Clinical Trials from the Last Decade - Assiri, Ahmad (Indian Journal of Pharmaceutical Education and Research)
Background: Alopecia areata (AA) is an autoimmune disorder with diverse clinical presentations and limited universally effective therapeutic options. Over the past decade, numerous treatment strategies have emerged, including Janus Kinase (JAK) inhibitors, corticosteroids, laser therapies, PRP (Platelet-Rich Plasma), and novel alternative agents. Objectives: To systematically review and synthesize clinical trial evidence from the last ten years evaluating treatment modalities for AA with a focus on efficacy, safety, route of administration, and innovation. Materials and Methods: A comprehensive literature search was conducted across databases, including PubMed, Scopus, and Web of Science, for clinical trials published between 2015 and 2025. Studies were selected based on the predefined PRISMA criteria. Data on the study design, interventions, control treatments, sample size, and outcomes were extracted and analyzed descriptively. Among the retrieved articles, 108 met the inclusion criteria. Results: Treatments included oral and topical JAK inhibitors (e.g., baricitinib and ritlecitinib), intralesional corticosteroids, minoxidil, PRP, biologics, and alternative therapies. Oral JAK inhibitors showed the most consistent efficacy, particularly in patients with extensive AA, but they required continuous administration. Intralesional corticosteroids remained an effective option, while PRP and alternative treatments showed variable but promising outcomes. Laser and light therapies are effective adjuncts to certain regimens. Conclusion: There is an increasing therapeutic diversity for AA, with oral JAK inhibitors emerging as a key option for severe cases. However, the treatment response varies according to the patient profile, formulation, and delivery route. More high-quality long-term studies are needed to guide personalized treatment plans.
Keywords: Alopecia areata; Janus Kinase Inhibitors; Systematic Review; Hair Regrowth; Treatment Modalities.